Towards more drug-like proteomimetics: two-faced, synthetic α-helix mimetics based on a purine scaffold1. Issue 32 (28th August 2015) - Lanning, M. E.; Wilder, P. T.; Bailey, H.; Drennen, B.; Cavalier, M.; Chen, L.; Yap, J. L.; Raje, M.; Fletcher, S.
<x xml:space="preserve">Abstract</x> Key residues on opposing faces of the Bak-BH3 α-helix were recapitulated by the 2, 6, 9-tri-substitution of a purine scaffold.